An Analysis of the Wakalah bil Ujrah Contract in Mountain Photo or Greeting Delivery (Jastip) Services on the Instagram Account Babangkiwill_ - Muhammad Ilham Sanusi; Malihatul Uyun; Nazma Maulidia Azzahra; Jaenudin J; Dian Herdiana (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the implementation of the wak?lah bil ujrah contract in the practice of photo or greeting delivery services (jastip) conducted by the Instagram account @Babangkiwill_, with a focus on the conformity of the contract elements to the principles of fiqh mu??malah. The research employs a descriptive qualitative method through observation of the account’s activities, interviews with service providers and users, as well as documentation of posts and digital transactions. A literature review of classical fiqh sources and previous research is also used to strengthen the analysis. The findings indicate that this jastip practice essentially meets the characteristics of a wak?lah bil ujrah contract, particularly in the aspects of delegated authority and compensation. However, it still requires clarity regarding the service object, transparency of the ujrah (fee), and avoidance of gharar and tadl?s to ensure compliance with sharia principles. This study demonstrates that classical contracts can adapt to the digital creative economy, as long as sharia principles are upheld.